PREFERENCES OF STUDENT RESIDENTS TOWARDS SUSTAINABILITY WITH THE CONCEPT OF BIOCLIMATIC DESIGN - Jamaludin, Adi Ainurzaman; Hussein, Hazreena; Keumala, Nila; Mohd Ariffin, Ati Rosemary (PLANNING MALAYSIA, 2016)
A satisfaction and perception survey was carried out at a residential college building in Kuala Lumpur. It was acknowledged as an energy efficient building due to the most considerate implementation of bioclimatic design concept. Currently, there is no specific preference studies were done in this type of building in the equatorial climate region. 266 respondents were received, relying on 95% confidence level and Â±5% margin of error from the overall population. The satisfaction and perception levels of residents are found to be positive with the concept of bioclimatic design. A majority of them are at a comfort level in all performance indicators including the internal courtyard, thermal comfort and indoor air quality, day lighting and landscape features, which contributed to the increased work productivity. Indirectly, it shows that the bioclimatic design concept at an old residential building is still appropriate to meet the needs of contemporary life while increasing the efficiency of electricity usage. Nevertheless, the positions of the rooms should be highly considered in implementing the improvement measures for increasing the comfort level of the room when this aspect, rather than the gender aspect, considerably influences the satisfaction and perception levels of respondents.